2021
DOI: 10.1016/j.jcjo.2020.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral interstitial keratitis as the presenting manifestation of systemic lupus erythematosus in a child

Abstract: Bilateral interstitial keratitis as the presenting manifestation of systemic lupus erythematosus in a child Q1 X X Interstitial keratitis (IK) is defined as a nonsuppurative inflammation of the corneal stroma with associated cellular infiltration and vascularization commonly caused by infections or rheumatologic conditions. Although extremely rare, IK may be seen with systemic lupus erythematous (SLE). We present the first case of a child without known history or symptomatology of rheumatologic or infectious d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“… 9 Recently, Abbas et al reported a case of bilateral interstitial keratitis in a 9-year-old girl with SLE. 7 The lesions in our cases were not associated with PUK or other ocular surface or intraocular inflammation.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“… 9 Recently, Abbas et al reported a case of bilateral interstitial keratitis in a 9-year-old girl with SLE. 7 The lesions in our cases were not associated with PUK or other ocular surface or intraocular inflammation.…”
Section: Discussionsupporting
confidence: 45%
“… 5 There have been reports of acute corneal stromal infiltration and edema in systemic lupus erythematosus (SLE) patients and diffuse stromal opacification in patients with ATS, but there are no reports on peripheral corneal deposits with neovascularization, similar to that seen in Terrien's marginal degeneration (TMD). 2 , 6 , 7 , 8 , 9 , 10 In this observational case series, we report two cases of refractile, peripheral, corneal stromal deposition in patients with ATS and EDS, two closely related CTDs.…”
Section: Introductionmentioning
confidence: 97%